Nitride alloy layer formation of duplex stainless steel using nitriding process - Maleque, Md. Abdul; Lailatul, P.H.; Fathaen, A. A.; Norinsan, K.; Haider, Julfikar (IOP Publishing, 2018)
Duplex stainless steel (DSS) shows a good corrosion resistance as well as the mechanical properties. However, DSS performance decrease as it works under aggressive environment and at high temperature. At the mentioned environment, the DSS become susceptible to wear failure. Surface modification is the favourable technique to widen the application of duplex stainless steel and improve the wear resistance and its hardness properties. Therefore, the main aim of this work is to nitride alloy layer on the surface of duplex stainless steel by the nitriding process temperature of 400°C and 450°C at different time and ammonia composition using a horizontal tube furnace. The scanning electron microscopy and x-ray diffraction analyzer are used to analyse the morphology, composition and the nitrided alloy layer for treated DSS. The micro hardnesss Vickers tester was used to measure hardness on cross-sectional area of nitrided DSS. After nitriding, it was observed that the hardness performance increased until 1100 Hv0.5kgf compared to substrate material of 250 Hv0.5kgf. The thickness layer of nitride alloy also increased from 5μm until 100μm due to diffusion of nitrogen on the surface of DSS. The x-ray diffraction results showed that the nitride layer consists of iron nitride, expanded austenite and chromium nitride. It can be concluded that nitride alloy layer can be produced via nitriding process using tube furnace with significant improvement of microstructural and hardness properties.